2022
DOI: 10.1039/d1cc06611k
|View full text |Cite
|
Sign up to set email alerts
|

A PET-based fluorescent probe for monitoring labile Fe(ii) pools in macrophage activations and ferroptosis

Abstract: A fluorescent probe (COU-LIP-1) for monitoring labile Fe(II) pools (LIP) with high selectivity and sensitivity was developed utilizing coumarin 343 as the fluorophore and 3-nitrophenylazanyl ester as both the reactive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Finally, imaging with Ac−H−FluNox demonstrated that the labile heme level was upregulated upon the induction of ferroptosis by erastin in HT−1080 cells. Similarly, Xing et al [45] reported another selective reaction−based probe COU−LIP−1 by the Fe 2+ −triggered N−O bond cleavage and applied it for monitoring intracellular labile Fe 2+ pools (Figure 5). COU−LIP−1 was designed by utilizing coumarin 343 as the fluorophore and 3−nitrophenylazanyl ester as both the recognition group and the fluorescence quenching group.…”
Section: Probes For Fe 2+ and Hemementioning
confidence: 96%
“…Finally, imaging with Ac−H−FluNox demonstrated that the labile heme level was upregulated upon the induction of ferroptosis by erastin in HT−1080 cells. Similarly, Xing et al [45] reported another selective reaction−based probe COU−LIP−1 by the Fe 2+ −triggered N−O bond cleavage and applied it for monitoring intracellular labile Fe 2+ pools (Figure 5). COU−LIP−1 was designed by utilizing coumarin 343 as the fluorophore and 3−nitrophenylazanyl ester as both the recognition group and the fluorescence quenching group.…”
Section: Probes For Fe 2+ and Hemementioning
confidence: 96%
“…16). 140 In this probe, coumarin 343 was used as skeleton, and the 3-nitrophenylazanyl ester simultaneously served as Fe 2+ reactive site and quenching moiety. Based on the PET mechanism, probe 20 emitted faint fluorescence emission due to the quenching effect of 3-nitrophenylazanyl ester.…”
Section: Small-molecule Fluorescent Probes For Monitoring Iron Ions U...mentioning
confidence: 99%
“…The appearance of the peak at 7.85 ppm, 7.78 ppm (−CH 2 −NH−), and 3.60 ppm (−CH 2 −NH−) in 1 H NMR and the peaks at 132 and 38.2 ppm suggested the successful reaction of the carboxyl-containing triphenylphosphine with the amino group. The appearance of the peak at 3.80 ppm (−CH 2 −N) in 1 H NMR and 50.52 ppm (−CH 2 −N) in 13 C NMR suggested the successful reaction of the naphthalimide with the amino group. The above NMR information proved that Si-Mito-ONOO was successfully synthesized.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We characterized by using 1 H NMR and 13 C NMR. The appearance of the peak at 3.72 ppm (−CH 2 −N) in 1 H NMR and 48.15 ppm in 13 C NMR implied that Si-Lyso-ONOO was successfully synthesized. The appearance of the peak at 7.85 ppm, 7.78 ppm (−CH 2 −NH−), and 3.60 ppm (−CH 2 −NH−) in 1 H NMR and the peaks at 132 and 38.2 ppm suggested the successful reaction of the carboxyl-containing triphenylphosphine with the amino group.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation